Insights into electronic properties of strained two-dimensional semiconductors by out-of-plane bending. (19th July 2023) - Chen, Daohong; Wang, Leixi; Lv, Yawei; Liao, Lei; Li, Kenli; Jiang, Changzhong
Abstract: Strain engineering is an important strategy to modulate the electronic and optical properties of two-dimensional (2D) semiconductors. In experiments, an effective and feasible method to induce strains on 2D semiconductors is the out-of-plane bending. However, in contrast to the in-plane methods, it will generate a combined strain effect on 2D semiconductors, which deserves further explorations. In this work, we theoretically investigate the carrier transport-related electronic properties of arsenene, antimonene, phosphorene, and MoS2 under the out-of-plane bending. The bending effect can be disassembled into the in-plane and out-of-plane rolling strains. We find that the rolling always degrades the transport performance, while the in-plane strain could boost carrier mobilities by restraining the intervalley scattering. In other words, pursuing the maximum in-plane strain at the expense of minimum rolling should be the primary strategy to promote transports in 2D semiconductors through bending. Electrons in 2D semiconductors usually suffer from the serious intervalley scattering caused by optical phonons. The in-plane strain can break the crystal symmetry and separate nonequivalent energy valleys at band edges energetically, confining carrier transports at the Brillouin zone Γ point and eliminating the intervalley scattering. Investigation results show that the arsenene and antimonene are suitable for the bending technology, because of their small layer thicknesses which can relieve the rolling burden. Their electron and hole mobilities can be doubled simultaneously, compared with their unstrained 2D structures. From this study, the rules for the out-of-plane bending technology towards promoting transport abilities in 2D semiconductors are obtained.